Evaluation of a community-based HIV test and start program in a conflict affected rural area of Yambio County, South Sudan. - Cecilia Ferreyra; Laura Moretó-Planas; Fara Wagbo Temessadouno; Beatriz Alonso; Buai Tut; Victoria Achut; Mohamed Eltom; Endashaw M Aderie; Vicente Descalzo-Jorro; Vicente Descalzo-Jorro (PLoS ONE)
Background Antiretroviral therapy (ART) coverage in South Sudan is around 10%. Access to HIV care in settings with low ART coverage or conflict affected is still low; innovative strategies are needed to increase access and ensure continuation of ART during instability. A pilot HIV test and start project was implemented in a conflict-affected area of South Sudan. In a retrospective analysis, we determined the feasibility and outcomes of this intervention. Methods Programme data from July 2015 to June 2018 was analysed. The project involved five mobile teams offering HIV counselling and testing (HCT) and same day ART initiation at community level. Baseline and follow-up information on clinical, immunological and viral load (VL) was routinely recorded, as well as treatment outcomes. A semi-qualitative study was conducted to assess acceptability of the program among beneficiaries and community members. Results By June 2018, 14824 people received counselling and testing for HIV and 498 (3.4%) tested positive. Out of those 395 (79.3%) started ART. A total of 72 ART patients were organized in 26 Community ART Groups (CAGs) and contingency plan was activated 9 times for 101 patients. Kaplan-Meier estimated retention in care (RIC) at 12 and 18 months was 80.6% [95% CI: 75.9-84.5%] and 69.9% [95% CI: 64.4-74.8%] respectively. RIC was significantly higher at 18 months in patients under community ART groups (CAGs) (90.9% versus 63.4% p<0.001) when compared to patients on regular follow up. VL suppression at 12 months was 90.3% and overall virological suppression reached 91.2%. A total of 279 persons were interviewed about the MSF program perception and acceptance: 98% had heard about the programme and 84% found it beneficial for the community, 98% accepted to be tested and only 4% found disadvantages to the programme. Conclusions Our study shows that HCT and early ART initiation in conflict affected populations can be provided with good program outcomes. RIC and virological suppression are comparable with facility-based HIV programs and to those in stable contexts. This model could be extrapolated to other similar contexts with low access to ART and where security situation is a concern.